Leveraging the Facebook Ads Platform for Election Polling - Ribeiro, Filipe N.; Kansaon, Daniel; Benevenuto, Fabrício (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Election polls provide valuable insights about voting intention on candidates filtered by demographic characteristics. This information can be used to understand the dynamics of underlying electoral preferences and how it changes in the days or months during the campaign. Despite its importance, election polls are time and money consuming on many occasions. Especially those with face-to-face surveys, that interview a representative population of the voters across the entire country. In this study, we propose a novel approach that explores social media advertising platforms to infer the audience demographics of politicians in the electoral race. We leverage the attribute-based targeting available on the Facebook Advertising platform by using the ‘interests’ related to candidates to calculate their audience demographics. Then, we compared the online extracted data with election polls taken in the same period. Our findings suggest that the candidate’s popularity on Facebook, captured in terms of the number of likes, people talking about him/her, and the number of people interested in the candidate, is a valid indicator of his/her variation on vote intention polls. Additionally, we figured out that the fluctuation in the demographic aspects of supporters detected by election polls are captured by our methodology, obtaining more precision with popular candidates. In particular, we show that sharp variations occasioned by high impact events during the campaign such as protests are well captured by Facebook measurements. Finally, we deployed a system that exposes the audience demographics of Brazilian politicians on Facebook (available at http://www.audiencia-dos-politicos.dcc.ufmg.br/ ) and contributes to the understanding of the political scene in Brazil.